SIFAT PEMESINAN 10 JENIS KAYU DARI DAERAH NUSA TENGGARA BARAT - Osly Rachman; Sri Rulliaty (Jurnal Penelitian Hasil Hutan, 1990)
Machining  properties  of  ten  wood  species from West Nusa Tenggara is reported  in this paper.The sample material was tested under ASTM D-1666 that was modified   according to  Forest Products Research  Institute Report No.160 (1982). The  samples (25  pieces/species) were  dried  to  equilibrium   moisture content condition (15 to18 %  of  MC). The  machining  properties   tested  are planing,  shaping,  boring,  turning,  and sanding.Four species  that have good  to  very good  machining properties  are Anthocephalus cadamba  Miq., Duabanga moluccana BL., Eugenia longiflora (Presl.) F. Viii., and  Eugenia polyantha Wight. Whereas the other species have poor  machining properties   i.e.,  Ailanthus  malabarica DC, Ficus  microcarpa   L.f  and  Palaquium  javense Burck.